Comparison of Five Parathyroid Scintigraphic Protocols. (21st January 2013) - Tunninen, Virpi; Varjo, Pekka; Schildt, Jukka; Ahonen, Aapo; Kauppinen, Tomi; Lisinen, Irina; Holm, Anu; Eskola, Hannu; Seppänen, Marko
Abstract : Objectives . We compared five parathyroid scintigraphy protocols in patients with primary (pHPT) and secondary hyperparathyroidism (sHPT) and studied the interobserver agreement. The dual-tracer method (T 99 m c-sestamibi/ 123 I) was used with three acquisition techniques (parallel-hole planar, pinhole planar, and SPECT/CT). The single-tracer method (T 99 m c-sestamibi) was used with two acquisition techniques (double-phase parallel-hole planar, and SPECT/CT). Thus five protocols were used, resulting in five sets of images. Materials and Methods . Image sets of 51 patients were retrospectively graded by four experienced nuclear medicine physicians. The final study group consisted of 24 patients (21 pHPT, 3 sHPT) who had been operated upon. Surgical and histopathologic findings were used as the standard of comparison. Results . Thirty abnormal parathyroid glands were found in 24 patients. The sensitivities of the dual-tracer method (76.7–80.0%) were similar (P = 1.0 ). The sensitivities of the single-tracer method (13.3–31.6%) were similar (P = 0.625 ). All differences in sensitivity between these two methods were statistically significant (P < 0.012 ). The interobserver agreement was good. Conclusion . This study indicates that any dual-tracer protocol withT 99 m c-sestamibi and 123 I is superior for enlarged parathyroid gland localization when compared with single-tracer protocols usingT 99 m c-sestamibi alone. The parathyroid scintigraphy was found to be independent of the reporter.